Implementasi Fuzzy Tsukamoto dalam Membangun Model Solar Tracking Otomatis - Tommy, Tommy; Irwan, Dedy (Sinkron : jurnal dan penelitian teknik informatika, 2018)
Solar energy is an alternative energy resource that has been widely used today. Solar panels or solar energy cells convert energy from sunlight into electrical energy which can be a pretty good alternative besides using fossil fuel which is full of pollution. To obtain optimal energy, the angle of the solar panel surface must be in the right position so that it can absorb the energy from the light source optimally, because light source like the sun is always moving. The implementation of intelligent systems such as Tsukamoto fuzzy can be implemented in addition to the development of solar tracking which can improve the performance of solar tracking based on the voltage value received and determine the angle of the solar panel surface to find the optimal light source. This study developed a solar tracking model with Tsukamoto fuzzy implementation to determine the optimal angle of the solar panel surface.